PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN SOSIAL TERHADAP MINAT BERWIRAUSAHA MAHASISWA S1 PENDIDIKAN EKONOMI FKIP UNTAN - Harianto, Gredy Hengrawi; Witarsa, Witarsa; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This researsh was conducted at The Faculty of Teacher Training and Education Tanjungpura University. The purpose of this research is to determine whether there is an influence from the family environment, influence from the social environment, and the influence from family and social environment on the students"™ enterpeneurial interest at Tanjungpura University. The model used in this research is quantitative research. The population of this research is the whole undergraduate students of the Economic Education Study Program class of 2018-2021. The sample used in this study is 138 people. The data collection technique in this research is indirect communication technique using questionnaire media. The result of this research show that the family environment has an influence of 71,44%, while the social environment has an influence of 68,6%. The family and social environment also have a simultaneuos influence with an F Test result value of 131.546. The conclusion of this research is family environment and social environment have an influence individually and simultaneously. The researcher suggests the students to create a positive environment and provide suppor so that the interest in enterpreneurship can be further increased in every individuals and can have a positive impact on society, and for students to be more active in developing themselves to be better.